Paragliding Recreational Sports Management in Mountain Panten, Majalengka Regency, West Java Province - Wulandari, Mida; Pramono, Harry; Rustiadi, Tri (Journal of Physical Education and Sports, 2022)
This study aims to analyze and describe the planning, organizing, movement, and control systems, which include Human Resources, Funding, Management, Facilities and Infrastructure, Program Activities, and Tourism Marketing. This study employs a qualitative descriptive approach. The research subjects are administrators, athletes/pilots, tourism and culture departments, and paragliding users. Techniques for data collection include observation, interviews, and documentation. Data triangulation was used as a technique for data analysis. The tandem paragliding athlete/pilot came from outside Majalengka Regency. Management Initially funded by the local government, now funded by visitor tickets. Management already has a well-defined organizational structure and management responsibilities. There are still insufficient tools to support tandem paragliding activities in Facilities and Infrastructure Management. The management of the activity program is consistent with the established activity program. Tourism Marketing Management has promoted tourism via social media, print media, and television broadcasts and in collaboration with tour and travel operators. According to the research, human resource management, management, activity program management, and tourism marketing management are all considered excellent. Meanwhile, both Funding Management and Facilities and Infrastructure Management remain deficient.